(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
The main goal of this study is to examine the feasibility of blind spot detection systems by using ultrasonic sensors. The blind spot detection systems will be used to identify obstacles inside the blind spot area. Hence, cautioning or alarming the driver consequently will secure the driver completely and prevent the driver from failure in identifying obstacles inside the blind spot region. The system mainly consists of the circuit connection of the Arduino UNO as the microcontroller and its software program. The usage of three ultrasonic sensors will be used for the system on each side of the vehicle with a 30-degree angle and in front of the vehicle to detect the incoming obstacle. To summarize the study, the constructed system is cheap, however, it is capable to help guiding the drivers from any lethal injuries from the blind spot region while on driving, especially when changing lanes on the road.